Spirituality and Spiritual Care in and Around Childbirth - Crowther, S; Hall, J (Elsevier, 2015)
Background: Emerging evidence points to childbirth as a spiritually felt meaningful occasion. Although growing literature and development of guidelines charge the midwife to provide spiritual care felt spiritual experiences are not addressed. There is need to revisit contemporary approaches to spiritual care in midwifery lest something of significance becomes lost in policy rhetoric. Aim: The aim of this discussion paper is to bring to the surface what is meant by spiritual care and spiritual experiences, to increase awareness about spirituality in childbirth and midwifery and move beyond the constraints of structured defined protocols. Methods: The authors' own studies and other's research that focuses on the complex contextual experiences of childbirth related to spirituality are discussed in relation to the growing interest in spiritual care assessments and guidelines. Findings: There is a growing presence in the literature about how spirituality is a concern to the wellbeing of human beings. Although spirituality remains on the peripheral of current discourse about childbirth. Spiritual care guidelines are now being developed. However spiritual care guidelines do not appear to acknowledge the lived-experience of childbirth as spiritually meaningful. Conclusion: Introduction of spiritual care guidelines into midwifery practice do not address the spiritual meaningful significance of childbirth. If childbirth spirituality is relegated to a spiritual care tick box culture this would be a travesty. The depth of spirituality that inheres uniquely in the experience of childbirth would remain silenced and hidden. Spiritual experiences are felt and beckon sensitive and tactful practice beyond words and formulaic questions.
Keywords: Childbirth; Meaning; Midwives; Spiritual care; Spirituality